O estilo de gestão das escolas municipais de Santa Maria como requisito para a qualidade - Griboski, Claudia Maffini (2004)
This study had, as its main objective, to verify if the municipal schools of Santa Maria possess differentiated administration practices that favor the democratization of school space, the modernization of its administration, and the students' effective learning. The research, characterized as a multi-case study, involves opinions and the perception of the municipal schools directors in a comprehensive qualitative and quantitative study. The data were collected seeking to identify if the schools are guided to a process of school conduct. In relation to organizational characteristics, the results demonstrated that the schools need a larger contribution of resources, as much as financial to improve its structures, as of personnel to promote its amplification and qualification in serving, with quality, the student body s diversity. The data allowed us to conclude that the schools, in their great majority, still accomplish school management practices. These are established in participative form and with the intention of answering to the community s school needs. It is important to point out, that the Municipal Educational District also develops school management practices, with its eyes accompanying the progress of the schools and contributing to the quality improvement of the educational process in the school system. Thus, when showing the important aspects of school administration, the results of the research allowed us to understand that the quality in managing education, as an educational principle, invests in favor of an education articulated to transformation, suggesting other studies with larger depth in this subject and specific learning in such context.